PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUASAN NASABAH IMPLIKASINYA PADA STRATEGI PEMASARAN PADA PT. BANK PERKREDITAN RAKYAT (BPR) PIJER PODI KEKELENGEN CABANG MEDAN - Tamba, Darwis; Purba, Betniar (UNIKA Santo Thomas, 2022)
The purpose of this study is to analyze the effect of the service marketing mix which includes product, price, place and promotion, process, people, and physical evidence on customer satisfaction. . The purpose of this study is expected to be able to overcome problems regarding the marketing mix of services which include product (product), price (price), place (place) and promotion (promotion), process (process), people (people), and physical evidence (physical evidence). its effect on customer satisfaction. The research method with a sample of 96 customers, questionnaire data collection techniques and documentation and analysis techniques with multiple linear regression. Based on the results of the study, the multiple linear regression equations are: Y = 4.200 + 0.359X1 + 0.433X2 + 0.261 X3 + 0.321X4 + 0.274X5 + 0.353X6 + 0.345X7. This means that product, price, place, promotion, process, people and physical evidence variables have a positive effect on customer satisfaction and the price dimension has a greater influence on customer satisfaction compared to product, people, physical evidence, process, promotion and place dimensions. The results of the F test show that the variables of product, price, place, promotion, process, people and physical evidence have a simultaneous and significant effect on customer satisfaction, this can be seen from the Fcount which is 25,047 then H0 is rejected and H1 is accepted. The results of the t-test, show that the variables of product, price, place, promotion, process, people and physical evidence have a partial and significant effect on customer satisfaction, then H0 is rejected and H1 is accepted. The value of the determinant coefficient (R Square) = 0.669 means that customer satisfaction can be explained by the service marketing mix (product, price, place, promotion, process, people and physical evidence) of 66.9% while 33.1% is explained by other factors that not described in this study such as safety and convenience. o increase customer satisfaction at BPR Pijer Podi Kekelengen Medan, it is better to make adjustments to those offered by competitors so that they continue to exist in the future